Osteoblasts behavior on chemically treated commercially pure titanium surfaces. Issue 6 (29th June 2013) - Oliveira, D. P.; Palmieri, A.; Carinci, F.; Bolfarini, C.
Abstract Surface modifications of commercially pure titanium (Cp‐Ti), a material widely used to produce dental implants, can induce specific responses on osteoblastic cells after implantation. This work aims to investigate the influence of chemically modified surfaces of Cp‐Ti by acid etching or acid etching plus alkaline treatment on the gene expression of human osteoblastic (Hob) cells. Roughness and contact angle measurements were carried out to evaluate the surface properties of the samples. The surface morphology was investigated with scanning electron microscopy. Chemical composition was analyzed by energy dispersive X‐ray spectroscopy (EDS). The expression levels of some bone‐related genes (ALPL, COL1A1, COL3A1, SPP1, RUNX2, and SPARC) were analyzed using real time Reverse Transcription‐Polymerase Chain Reaction (real time RT‐PCR). The results showed that all the chemical modifications studied in this work influenced the surface morphology, wettability, roughness and induced an osteoconductive behavior. The samples that were acid etched and alkaline treated showed a more pronounced effect. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1816–1822, 2014.